A revised method with a temperature constraint for assimilating satellite-derived humidity in forecasting sea fog over the Yellow Sea - Gao, Xiaoyu; Gao, Shanhong; Li, Ziru; Wang, Yongming (Frontiers in Earth Science, 2023)
Numerical forecast of sea fog is a very challenging work because of its high sensitivity to model initial condition. For better depicting the humidity structure of marine atmospheric boundary layer (MABL), Wang et al. assimilate satellite-derived humidity from sea fog at its initial stage over the Yellow Sea (W14 method), using an extended three-dimensional variational data assimilation (3DVAR) with the Weather Research and Forecasting Model (WRF). This paper proposes a revised version of the W14 method based on the study of Wang et al. The major ingredient of the revision is the inclusion of temperature constraint into the satellite-derived humidity, not only for missed fog that the W14 method primarily considers, but also for false fog that is ignored in the W14 method. The numerical experiment results of 10 sea fog cases over the Yellow Sea show that the revised method can effectively alleviate the wet bias occasionally occurred in the W14 method, significantly improve the temperature and humidity structure of MABL, and increase the equitable threat score of simulated fog area by about 15% relative to the W14 method. In addition, a detailed case study is conducted to illustrate the working mechanism of the revised method, including sensitivity experiments focusing on the roles of two kinds of background error covariance (CV5 and CV6) in the assimilation by the WRF-3DVAR. The results suggest that it is better to use the revised method with CV6 rather than CV5, due to the correlation between temperature and other control variables, especially humidity.